Peran Kurikulum Merdeka dalam Membentuk Akhlak Siswa Sekolah Dasar - Elvin Nadhiroh; Nila Rohana; Anis Wulandari; Muhammad Nofan Zulfahmi (Universitas Maritim AMNI Semarang, 2025)
The Merdeka Curriculum is a new innovation in the Indonesian education system which aims to give students the freedom to learn and emphasizes the importance of building character and moral values. This study investigates how a free curriculum contributes to the moral formation of students in elementary schools. Relevant sources, such as books, scientific articles and educational policy documents, were collected and analyzed through the literature study method in this research. This research found that a free curriculum, with a more contextual learning approach and involving students' active participation in real activities such as collaborative projects and extracurricular activities, helps students understand moral values ​​and apply them in everyday life. It is proven that parental and community involvement is also an important component in building student character. This research found that the free curriculum not only focuses on improving students' academic achievement but also strengthens moral and ethical values. Therefore, continuous development of this curriculum is necessary to achieve broad educational goals. It is hoped that this research will help educators, policy makers and other researchers improve the quality of education in Indonesia by providing guidance for maximizing the curriculum to achieve more comprehensive educational goals.